Associations between adverse childhood experiences and diabetes among middle-aged and older Chinese: a social-ecological perspective - Siyu Zhu; Leying Hou; Jiaying Ma; Shuting Li; Weidi Sun; Wen Liu; Jiajun Hao; Wenhan Xiao; Siqing Cheng; Dexing Zhang; Dong Zhao; Peige Song (Epidemiology and Health, 2023)
OBJECTIVES This study examined the associations between adverse childhood experiences (ACEs) and diabetes within a social-ecological framework, incorporating personal and environmental unfavorable conditions during childhood from family, school, and community contexts. METHODS Data were obtained from the China Health and Retirement Longitudinal Study (2014 life history survey and 2015 survey), including 9,179 participants aged ≥45 years. ACEs were collected through self-report questionnaires, and participants were categorized based on the number of distinct ACEs experienced (0, 1, 2, 3, or ≥4 ACEs). Diabetes was defined by biomarkers, self-reported diagnosis, and treatment status. Logistic regression was conducted to explore the associations between ACEs and diabetes. Subgroup analyses were conducted by gender, age, and obesity status. RESULTS Compared with participants without ACEs, those exposed to any ACE (odds ratio [OR], 1.19; 95% confidence interval [CI], 1.01 to 1.40), 3 ACEs (OR, 1.32; 95% CI, 1.07 to 1.62) and ≥4 ACEs (OR, 1.29; 95% CI, 1.07 to 1.56) had an increased risk of diabetes. For each additional ACE, the risk of diabetes increased by about 5%. Regarding the source of ACEs, those originating from the family (OR, 1.23; 95% CI, 1.08 to 1.41) were associated with diabetes. In terms of specific ACE types, family members with substance abuse (OR, 1.23; 95% CI, 1.01 to 1.52), emotional abuse (OR, 1.28; 95% CI, 1.12 to 1.46), and poor parental relationship (OR, 1.25; 95% CI, 1.09 to 1.43) were associated with diabetes. CONCLUSIONS ACEs, particularly those originating from the family, were associated with diabetes. Interventions aimed at preventing and mitigating ACEs are essential for the early prevention of diabetes.